Highly swollen liquid crystals as new reactors for the synthesis of nanomaterials - Surendran, G.; Tokumoto, M. S.; dos Santos, E. P.; Remita, H.; Ramos, L.; Kooyman, P. J.; Santilli, Celso Valentim [UNESP]; Bourgaux, C.; Dieudonne, P.; Prouzet, E. (Amer Chemical Soc, 2005)
Synthesis and self-assembly of nanomaterials can be controlled by the properties of soft matter. on one hand, dedicated nanoreactors such as reverse microemulsions or miniemulsions can be designed. on the other hand, direct shape control can be provided by the topology of liquid crystals that confine the reacting medium within a specific geometry. In the first case, the preparation of micro- or miniemulsions generally requires energetic mechanical stirring. The second approach uses thermodynamically stable systems, but it remains usually limited to binary (water + surfactant) systems. We report the preparation of different families of materials in highly ordered quaternary mediums that exhibit a liquid crystal structure with a high cell parameter. They were prepared with the proper ratios of salted water, nonpolar solvent, surfactant. and cosurfactants that form spontaneously swollen hexagonal phases. These swollen liquid crystals can be prepared from all classes of surfactants (cationic, anionic, and nonionic). They contain a regular network of parallel cylinders, whose diameters can be swollen with a nonpolar solvent, that are regularly spaced in a continuous aqueous salt solution. We demonstrate in the present report that both aqueous and organic phases can be used as nanoreactors for the preparation of materials. This property is illustrated by various examples such as the synthesis of platinum nanorods prepared in the aqueous phase or zirconia needles or the photo- or gamma-ray-induced polymerization of polydiacetylene in the organic phase. In all cases, materials can be easily extracted and their final shapes are directed by the structure-directing effect imposed by the liquid crystal.